A complex structure representation of the US critical infrastructure protection program based on the Zachman framework. (3rd October 2019) - Tatar, Unal; Karabacak, Bilge; Katina, Polinpapilinho F.; Igonor, Andy
Critical infrastructures are vital assets for public safety, economic welfare or national security of countries. The importance of critical infrastructures necessitates state-level coordination of security efforts based on some rigid policies, strategies, and procedures. This hierarchical set of rules is collectively referred to as the critical infrastructure protection program (CIPP). As the pioneer of CIPP, the USA has a very complex program in which partners and stakeholders have multiple and varied interacting roles and responsibilities. The complexity of roles and interactions creates a need to make a representation of these complex structures by using intuitive tools. The Zachman framework is such a tool that provides a formal and structured way of viewing and defining a complex enterprise. It is represented by a 6×6 matrix with rows defining stakeholders and columns defining underlying interrogatives. In this article, a proof-of-concept study is performed to represent the US CIPP using the Zachman framework. The proof-of-concept study showed that the Zachman framework could be beneficial in overcoming challenges of a CIPP program which can be regarded as a complex enterprise.